Tourist itineraries for Sustainable Mobility: an application in the Salento Area (Italy) - Barbara Trincone (European Scientific Journal, ESJ, 2024)
In the framework of the 2014/2020 Interreg V-A Greece-Italy cross-border cooperation strategic project called "AI SMART_Adriatic Ionian Small Port Network", two itineraries have been defined for the interaction of the port of Otranto with the hinterland territories and with the opposite Ionian coast in order to promote the sustainable and inclusive transnational tourist fruition of the Apulian territory. The genesis of the two thematic itineraries stems from the need/willingness to valorise some areas of the Salento through the connection of significant nodes in terms of landscape, architectural and historical value, which define two routes with Pulsano and Otranto as their vertices. The project brings together the potential of the Salento as an area with a strong tourist value, with the theme of sustainable mobility.